The Influence Of Service Quality And Physical Evidence On Student Satisfaction Potensi Utama University - Syukron Hidayat Pane; Ari Prabowo (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
Currently, society's need for education continues to increase from time to time. The increasingly advanced level of life in society causes competition for human resources to become increasingly fierce. The increasing need of society for the importance of knowledge, encourages them to take educational levels from the lowest level to the highest level. To find out whether Service Quality has a positive and significant effect on student satisfaction at Potensi Utama University. To determine the effect of Physical Evidence on student satisfaction at Potensi Utama University. To find out how Service Quality and Physical Evidence simultaneously influence student satisfaction at Potensi Utama University. The method used in this research uses a method, namely the type of research used in this research is a quantitative research method. The population in this study was all students at Stambuk Potensi Utama University in 2023 totaling 1253 students. The sampling technique uses the Slovin formula, namely 92 rounded up to 100 people. The results of this research are (1) Service Quality partially has a positive and significant effect on Student Satisfaction, (2) Physical Evidence partially has a positive and significant effect on Student Satisfaction (3) Service Quality, and physical evidence together or simultaneously have a positive effect and significant to the satisfaction of Potensi Utama University Students.